Pedagogy of Petroleum English course, part B: A correlational investigation between learning motivations and learning achievements of Chinese students under MOOC-based blended modality - TCHAMENI, ALAIN PIERRE; Nagre, Robert Dery (Journal of English Language Teaching and Applied Linguistics, 2025)
The massive open online course MOOC-based blended learning modality has gained widespread academic recognition across various fields due to the enhancement of the academic performance of students. This research focuses on exploring the learning achievements of Chinese students, who showed improved academic performance in the petroleum English course under the MOOC-based blended learning modality compared to the traditional face-to-face modality, as reported in our previous study. However, the learning motivations that contributed to their learning achievements remain unsettled. Based on exploring the correlation between the Chinese sophomore year engineering students' learning motivations in the petroleum English course and learning achievements under the MOOC-based blended learning modality, this work aimed to examine the learning motivations that permitted enhanced learning achievements. For that purpose, a series of questionnaires was given to 216 Chinese sophomore year engineering students, among whom 8 were interviewed. Based on a series of statistical analyses of the responses provided by the students, the exploratory factor analysis, reliability test, statistical description, and correlational analyses, the relationship between the learning motivations and learning achievements was assessed. The results showed that the students were both positively intrinsically and extrinsically motivated, which was conducive to fostering the learning achievements, but the extrinsic motivations, having the descriptive aspects of getting a high-paying position, significantly contributed to this trend, based on the results of the loading factor. As a result, a stronger statistical correlation between the extrinsic motivations and learning achievements [ca. R2=0.601 with Sig. (2-tailed)